Collective Narcissism, In-Group Satisfaction, and Solidarity in the Face of COVID-19. Issue 6 (August 2021) - Federico, Christopher M.; de Zavala, Agnieszka Golec; Baran, Tomasz
The present study explored the antecedents of solidarity amid the COVID-19 pandemic. Given that solidarity during mass emergencies involves the development of a social identity encompassing those facing a common fate, we examined how national in-group satisfaction (IS, a belief that the national in-group and one's membership in it are of high value) versus national collective narcissism (CN, a belief that the national in-group is exceptional and entitled to privileged treatment but not sufficiently recognized by others) predicted solidarity with those affected by the pandemic in Poland. The results of cross-sectional and dynamic analyses from a panel study on a representative sample of Polish adults indicate that IS predicted greater COVID-19 solidarity, whereas CN predicted reduced COVID-19 solidarity.